Motivation and Language Learning: A Literature Review - Fithriyah Fithriyah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
Motivation plays an important role in human life. Some people succeed and others fail in their life because of their motivation. This condition has attracted many experts to study it. They have proposed some concepts of motivation, the role and its influence especially in learning. It also encourages language expertise to investigate the effect of motivation and its correlation in language learning. These phenomena prompted this study to explore the theoretical views of motivation and its connection to language learning. Data collected from various books and journals that were related to the study. Furthermore, the implication to the language learning was explained on discussion section.